DOMINASI KECERDIKAN DAN KEPEMIMPINAN STRATEGIS PEREMPUAN DI DRAMA KOREA QUEEN MAKER DARI RESEPSI KHALAYAK - Azzahra, Adinda Febriyan; Dwijayanti, Risqi Inayah; Marta, Rustono Farady; Olivia, Helen; Saliman, Timotius (Universitas Gunadarma, 2024)
The media can influence public perceptions of gender roles, including the role of women in leadership positions. The Korean drama ‘Queen Maker’ is an interesting example of the role of visual media in portraying women's struggle for gender equality. Exploring audience reactions to this drama is important to understand how the media can change public perceptions of women's leadership. The theoretical basis for this study is Stuart Hall's Audience Reception Theory. It draws on the concepts of film as mass communication, women in leadership, gender, feminism, stereotypes, and patriarchal culture. This study uses a qualitative approach with a reception analysis method. The data collection tool used is Forum Group Discussion (FGD), a constructivist paradigm with data analysis that includes data reduction activities, data presentation and inference. The results of FGD show that each informant has a meaning (decoding) that can be categorised into three positions: Dominance, Negotiation and Opposition. The results of the study suggest that audiences have a dominant understanding of the portrayal of female leadership in drama, that the female leadership portrayed in the Korean drama Queen Maker shows the resourcefulness and strategic abilities of women in achieving political goals.